2020
DOI: 10.1021/jacs.0c04034
|View full text |Cite
|
Sign up to set email alerts
|

Fast Proton Transfer and Hydrogen Evolution Reactivity Mediated by [Co13C2(CO)24]4–

Abstract: A common approach to speeding up proton transfer (PT) by molecular catalysts is manipulation of the secondary coordination sphere with proton relays and these enhance overall reaction rates by orders of magnitude. In contrast, heterogeneous electrocatalysts have band structures that promote facile PT concerted with electron transfer (ET), known as the Volmer mechanism. Here, we show that [Co13C2(CO)24]4–, containing multiple Co–Co bonds to statistically enhance observed rates of PT, promotes PT on the order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…The fast rate for PT1 is also consistent with our previous report of fast PT by 2 4À where we reported that k PT1 = 2.3 × 10 9 M À 1 s À 1 , with an overpotential of 760 mV. [19] Both 1 3À and 2 4À have many CoÀ Co bonds making up their surface and these serve as many sites for PT which statistically enhances the rate of PT1 just like a proton relays in a molecular catalyst enhance PT rates. Similarly, heterogeneous catalysts routinely display fast PT via the Volmer mechanism.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The fast rate for PT1 is also consistent with our previous report of fast PT by 2 4À where we reported that k PT1 = 2.3 × 10 9 M À 1 s À 1 , with an overpotential of 760 mV. [19] Both 1 3À and 2 4À have many CoÀ Co bonds making up their surface and these serve as many sites for PT which statistically enhances the rate of PT1 just like a proton relays in a molecular catalyst enhance PT rates. Similarly, heterogeneous catalysts routinely display fast PT via the Volmer mechanism.…”
Section: Resultssupporting
confidence: 89%
“…It is known that a linear correlation exists between ν CO and z/M, where z is the cluster charge, and M is the number of cobalt atoms; and this relationship holds true over cobalt carbide carbonyl clusters with 2-13 cobalt atoms and charge À 1 to À 4 (Figure 1 bottom). [19,21] We generated 1 3À in situ using one equivalent of cobaltocene as a reductant in acetonitrile. The IR spectrum displayed absorption bands at 1974 and 1768 cm À 1 which are lower in energy, as expected for a more electron rich cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic properties of carbide clusters for hydrogen evolution has been reported. [19] Prospectus. The convertibility of [Fe 6 C(CO) 14 S] 2into clusters that more closely resemble FeMoco remains an intriguing but challenging opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…Fe-C1: Fe6-C1, 1.866(6); Fe1-C1, 1.879(6); Fe2-C1, 1.896(6); Fe3-C1, 1.909(6); Fe4-C1, 1.909(6); Fe5-C1, 1.907(6). Fe-S1: Fe7-S1, 2.1612(19); Fe6-S1, 2.174(2); Fe3-S1, 2.1998 (19). -1 , similar to that of [5] 2-) is quite distinct from that of the precursor.…”
Section: Eurjicmentioning
confidence: 97%